APPLICATION OF SCROTAL ULTRASOUND IMAGING IN CLINICOPATHOLOGICALLY SUSPECTED CASES OF MALE INFERTILITY – A PROSPECTIVE STUDY IN A PERIPHERAL MEDICAL COLLEGE IN WEST BENGAL - PRASUN DAS (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to identify various scrotal and extra-scrotal factors with the use of scrotal ultrasound causing male infertility and their correlation with clinical and radiological findings. Methods: This prospective cross-sectional study was done on 100 male patients having suspected infertility referred to radiology department with clinical notes and pathological findings. All the patients underwent only scrotal ultrasonography with high frequency transducer having a frequency of 7.5 MHz and color Doppler wherever indicated. Results: In this study, most commonly detected etiology by clinical suspicion and ultrasound was varicocele. Ultrasound detected more etiologies compared to physical examination. Most commonly detected pathology both by clinical and scrotal ultrasound evaluation was varicocele. p-value was 0.0001 showing extreme statistical significance. Conclusion: Scrotal ultrasonography is important non-invasive diagnostic tools that minimize the need for more invasive studies in the evaluation of male infertility.